Leptospirose e toxoplasmose em primatas : diagnóstico molecular e estudo sorológico - Grumann, Marta Regina (2015)
This work describes a study of immunohistochemical and serological diagnosis of Leptospira spp. and Toxoplasma gondii infection, in nonhuman primates. In Chapter 1 the objective was detect animals infected with Leptospira spp., as well as observing the distribution of agent s immunostainings on tissues fragments. It was performed by immunohistochemistry (IHC) test, carried out on primates tissues, received at the Laboratório de Patologia Animal (LPA), Faculdade de Agronomia e Medicina Veterinária (FAMV) of the Universidade de Passo Fundo (UPF), for necropsy, between years 2000 and 2014. A serological study, in the captive primates of the Zoo UPF, was also conducted. Among the 101 primates tested by IHC for Leptospira spp., 51.48% were positive, with stainings distributed among lung (76.92%), liver (44.23%) and kidneys (32.69%). The detection of anti-Leptospira spp. antibodies, performed by microscopic agglutination test (MAT), has showed positivity in 90.47% in a population of 21 primates, with sejroe and panama serovars between the most frequent, obtaining a similarity of 20.83% each one. In the Chapter 2, similarly, the objective was to verify the presence and distribution pattern of T. gondii, in the tissues of primates received for necropsy, at the LPA of FAMV-UPF, at the same period. The test was performed by IHC. Among the 98 primates, tested for T. gondii, 26.53% showed positive immunostanings, with different distribution between lung (76.92%), liver (58.33%), heart (50%), brain (42,30%) and kidney (23.07%). A serological survey for T. gondii has been also performed in primates of the genus Sapajus and Alouatta, captives of the Zoo-UPF. The test was carried out by indirect hemagglutination (IHA), showing reactivity in 85.7% of animals, which all belonged to the genus Sapajus, while the three of Alouatta genera, presented themselves seronegative (14.3 %).In conclusion, the IHC allowed to detect the presence of Leptospira spp. and Toxoplasma gondii in the primates tissues, demonstrating be a test with high applicability in the post mortem leptospirosis and toxoplasmosis diagnosis. In addition, the neotropical primates of the Zoo-UPF, showed a high frequency of infection by these agents